The Impact of Trade on Environmental Quality and Sustainable Development in ASEAN Region - Razak, Abd. Rahman; Saudi, Nur Dwiana Sari; Fernandes, Adji Achmad Rinaldo; Idris, Aditya; Arnan Rahman, Andi Muhammad (International Journal of Energy Economics and Policy, 2025)
This study investigates the impact of trade on environmental quality and sustainable development in the ASEAN region, focusing on the long-term implications of trade liberalization under the ASEAN Free Trade Area (AFTA). While trade has played a central role in boosting economic growth and regional integration, concerns about its environmental consequences have intensified, particularly with rising carbon emissions, resource depletion, and ecological degradation. Using a dynamic Autoregressive Distributed Lag (ARDL) modeling approach, this study explores the relationship between trade openness, carbon dioxide (CO2) emissions, and adjusted net savings as proxies for environmental sustainability and sustainable development. The empirical findings reveal a significant and negative long-run relationship between trade openness and both CO2 emissions and adjusted net savings. This suggests that, without robust environmental and social safeguards, increased trade activities may exacerbate environmental degradation and compromise the region’s long-term development goals. In contrast, the short-run effects appear weaker and mostly insignificant, implying that the detrimental impacts of trade develop progressively over time. These results challenge the conventional assumption that trade liberalization automatically promotes sustainable development. In the context of ASEAN, trade-driven growth may undermine environmental commitments outlined in the Sustainable Development Goals (SDGs), particularly those related to climate action and responsible consumption. The study underscores the urgent need for ASEAN policymakers to integrate trade policy with comprehensive environmental regulations to ensure that economic integration aligns with sustainability principles and intergenerational equity.